Integrated liquid chromatography method in enantioselective studies: biodegradation of ofloxacin by an activated sludge consortium - Maia, Alexandra S. (2017)
tOfloxacin is a chiral fluoroquinolone commercialized as racemate and as its enantiomerically pure formlevofloxacin. This work presents an integrated liquid chromatography (LC) method with fluorescencedetection (FD) and exact mass spectrometry (EMS) developed to assess the enantiomeric biodegradationof ofloxacin and levofloxacin in laboratory-scale microcosms. The optimized enantioseparation condi-tions were achieved using a macrocyclic antibiotic ristocetin A-bonded CSP (150 × 2.1 mm i.d.; particlesize 5 m) under reversed-phase elution mode. The method was validated using a mineral salts mediumas matrix and presented selectivity and linearity over a concentration range from 5 g L−1(quantificationlimit) to 350 g L−1for each enantiomer. The method was successfully applied to evaluate biodegrada-tion of ofloxacin enantiomers at 250 g L−1by an activated sludge inoculum. Ofloxacin (racemic mixture)and (S)-enantiomer (levofloxacin) were degraded up to 58 and 52%, respectively. An additional degrad-able carbon source, acetate, enhanced biodegradation up to 23%. (S)-enantiomer presented the highestextent of degradation (66.8%) when ofloxacin was supplied along with acetate. Results indicated slightlyhigher biodegradation extents for the (S)-enantiomer when supplementation was done with ofloxacin.Degradation occurred faster in the first 3 days and proceeded slowly until the end of the assays. Thechromatographic results from LC-FD suggested the formation of the (R)-enantiomer during levofloxacinbiodegradation which was confirmed by LC–MS with a LTQ Orbitrap XL.